Comparison of Methods for Bifenthrin Residues Determination in Fermented Wheat Samples - Đorđević, Tijana M; Đurović, Rada D; Gajić Umiljendić, Jelena S (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Efficiency of three different sample preparation methods for GC/MS determination of bifenthrin residues in wheat (Triticum spelta) samples fermented by Lactobacillus plantarum was tested. The first method was based on a methanol:acetone=1:1 extraction folowed by a purification on columns containing mixture of aluminium oxide and activated charcoal slurry-packed and eluted with dichlormethane, the second was based on methanol:acetone=1:1 extraction folowed by the purification on florisil column and elution by ethil acetate:acetone=4:1, while the third tested method was based on a combination of the first two mentioned methods, thus methanol:acetone=1:1 extraction and clean-up throught columns filled with a mixture of aluminum oxide and activated charcoal slurrypacked and eluted with ethil acetate:acetone=4:1. The second method was the most effective for obtaining satisfactory recoveries for bifenthrin in a range of 79-83% for four fortification levels, with good reproducibility i.e. RSD% in a range of 2.2-7.4%. The chosen method was further optimized by assessing the optimum volume of elution solvent used during the clean-up procedures. The highest recovery of 82.1% was obtained after elution with 25 ml of solvent. Overall, two-step extraction with 25 ml of methanol:acetone=1:1 solvent mix for 30 min, followed by clean-up procedure through a glass column with florisil coupled with elution with 25 ml of ethyl acetate: acetone=4:1, allows simple, efficient and reliable GC/MS detection of bifenthrin residues from wheat grain fermented by L. plantarum.